Fundamentals of smart contract security - Ma, Richard; Gorzny, Jan; Zulkoski, Edward; Bak, Kacper; Mack, Olga V. (Computer engineering foundations, currents, and trajectories collection., 2019)
Smart contracts are an innovative application of blockchain technology. Acting as decentralized custodians of digital assets, they allow us to transfer value and information more effectively by reducing the need to trust a third party. By eliminating the need for intermediaries, smart contracts have the potential to massively scale the world economy and unleash the potential for faster and more effcient solutions than traditional systems could ever provide. But there's one catch: while blockchains are secure, smart contracts are not. Security vulnerabilities in smart contracts have led to over 250 million USD in value to be lost or stolen. For smart contract technology to achieve its full potential, these security vulnerabilities need to be addressed. Written by security experts at the forefront of this dynamic industry, this book teaches state-of-the-art smart contract security principles and practices. Help us secure the future of blockchain technology and join us at the forefront today.